Analyzing the performance and risk diversification benefits between real estate investment trusts and public listed property companies in Malaysia - Ban, Gabriel Jia Le; Gan, Wee Boon (2019)
The purpose of conducting this research project is to analyse the performance and risk diversification benefits between Real Estate Investment Trusts (REITs) and Public Listed Property Companies (PPLCs) in Malaysia. To acquire the objective of this research project, research questions and five hypotheses are developed as well as tested. Besides, each hypothesis is measure accordingly and results are explained in detail. Furthermore, literature review are included in this research project in order to provide a clearer understanding towards the performance and risk diversification benefits between Real Estate Investment Trusts (REITs) and Public Listed Property Companies (PPLCs) and justification towards the research questions and research problems. Secondary data were collected through Bloomberg financial software. By using the calculation and analytic tools, the result are compute into a table and discussed as well. Last but not least, the implication has been discussed to provide insight and useful information for investors. Besides, the limitation faced in this research will be noted and recommendations will establish to assist future researcher in handling those limitations.